Safety and Therapeutic Optimization of Lutetium-177 Based Radiopharmaceuticals - Typhanie Ladrière; Julie Faudemer; Elise Levigoureux; Damien Peyronnet; Cédric Desmonts; Jonathan Vigne (MDPI AG, 2023)
Peptide receptor radionuclide therapy (PRRT) using Lutetium-177 (177Lu) based radiopharmaceuticals has emerged as a therapeutic area in the field of nuclear medicine and oncology, allowing for personalized medicine. Since the first market authorization in 2018 of [¹⁷⁷Lu]Lu-DOTATATE (Lutathera®) targeting somatostatin receptor type 2 in the treatment of gastroenteropancreatic neuroendocrine tumors, intensive research has led to transfer innovative 177Lu containing pharmaceuticals to the clinic. Recently, a second market authorization in the field was obtained for [¹⁷⁷Lu]Lu-PSMA-617 (Pluvicto®) in the treatment of prostate cancer. The efficacy of 177Lu radiopharmaceuticals are now quite well-reported and data on the safety and management of patients are needed. This review will focus on several clinically tested and reported tailored approaches to enhance the risk-benefit trade-off of radioligand therapy. The aim is to help clinicians and nuclear medicine staff set up safe and optimized procedures using the approved 177Lu based radiopharmaceuticals.